A new species of Rhododendron (Ericaceae) from Baili Rhododendron nature reserve, NW Guizhou, China - Ma, Yongpeng; Chamberlain, David; Sun, Weibang; Zhang, Cahngqin (Phytotaxa, 2015)
Rhododendron Linnaeus (1753: 392) is one of the largest genera in the family of Ericaceae, which is subject to much ongoing taxonomic debate. About 1,025 species are recognized; these are distributed from the northern temperate zone, throughout tropical Southeast Asia, to northeastern Australia (Chamberlain et al. 1996). In China, there are 571 species classified in 6 subgenera, of which 405 species are endemic (Fang et al. 2005). Apart from Xinjiang and Ningxia, Rhododendrons have been documented in all other provinces (Ma et al. 2014; Wu et al. 2005).